Minimal repair and replacement policy for a complex system with different failure modes of the groups - Aliyu, Zaharaddeen; Yakasai, Bashir (International Journal of Applied Mathematical Research, 2014)
This study or research work considered a complex system whose components are grouped into two each with different failure type. The first group consists of components or devices that are repairable and replaceable at failure (type y) and the second group consist of components that are non-repairable but replaceable at failure (type z). We rectify the defect of first group using minimal repair with probability p and replacement with probability 1-p at some threshold number n+1, n?1 of the minimal repair, whereas for components at second group we adopt only replacement in order to correct the failure of the components. Cost functions of the model are derived and both analytical and empirical realizations are made. Keywords: Repairable, Replaceable, Replacement and Minimal Repair.